2020
DOI: 10.1177/1558944720930298
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Flexor Tenosynovitis Following Trigger Finger Release: Incidence and Risk Factors

Abstract: Background: Trigger finger release (TFR) is one of the most commonly performed hand procedures and typically results in restoration of normal finger function. However, uncommon postoperative complications such as deep infection can have devastating consequences. The goal of this study was to evaluate the incidence, risk factors, and characteristics of infectious flexor tenosynovitis occurring after TFR. Methods: We searched billing records for the Current Procedural Terminology code for TFR to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…In 1933, Kanavel developed four cardinal signs to diagnose tenosynovitis, including symmetrical swelling of the whole finger, profound tenderness along the finger's length, semi flexed finger and extreme pain with passive extension of the affected finger. Staphylococcus aureus is the most common cause of tenosynovitis (Stewart & Ward, 2020). However, the incidence of tenosynovitis by GBS is unknown in the local setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1933, Kanavel developed four cardinal signs to diagnose tenosynovitis, including symmetrical swelling of the whole finger, profound tenderness along the finger's length, semi flexed finger and extreme pain with passive extension of the affected finger. Staphylococcus aureus is the most common cause of tenosynovitis (Stewart & Ward, 2020). However, the incidence of tenosynovitis by GBS is unknown in the local setting.…”
Section: Discussionmentioning
confidence: 99%
“…Tenosynovitis is most often an infection caused by gram-positive bacterial infections. Most cases of tenosynovitis are caused by Staphylococcus aureus, which accounts for 80% of all cases (Stewart & Ward, 2020). However, group B streptococcal soft tissue infections, which often lead to septicaemia and amputation in immunocompromised patients such as inflammatory arthritis, diabetes, cancer, and others, have been on the rise, which ranged from 13.9% to 38% (Pang et al, 2007;Karunakaran et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kirby et al demonstrated a much higher rate of infection after CTR if a corticosteroid injection had been administered preoperatively (mean, 55 days) 44 . Suppurative flexor tenosynovitis is a rare but serious complication after trigger finger release surgery 45 , and corticosteroid injection within 30 days prior to trigger finger release portends an elevated risk of deep infection requiring surgical debridement. In addition, there is an elevated risk of surgical site infection of any type when a corticosteroid injection had been administered within 90 days prior to a trigger finger release surgery 46,47 .…”
Section: Infectionmentioning
confidence: 99%
“…Selten sind auch postoperative Infektionen, z. B. nach A1-Ringbandspaltung [5]. Auch Bissverletzungen durch Tiere oder Menschen sind nicht selten [6].…”
Section: äTiologieunclassified